Aftershock fragility assessment of steel moment frames with self-centering dampers. (1st August 2018) - Silwal, Baikuntha; Ozbulut, Osman E.
Highlights: Steel buildings with a self-centering damper are analyzed under seismic sequences. Aftershock IDA analyses for the mainshock-damaged structures are carried out. The effect of aftershock ground motion polarity on the results are also explored. Steel frame with self-centering damper significantly improves aftershock capacity. Abstract: This study explores the aftershock collapse performance of steel buildings designed with superelastic viscous dampers (SVDs) under seismic sequences. The SVD strategically combines shape memory alloy (SMA) cables and a viscoelastic compound to provide good self-centering and damping capabilities. A nine-story steel special moment resisting frame (SMRF) is first designed with or without SVDs to satisfy modern seismic design requirements. A mainshock incremental dynamic analysis (IDA) is conducted for the SMRF and SVD frames using a total of ten as-recorded seismic sequences. The specific levels of post-mainshock interstory drift ratios are then induced in both frames and an aftershock IDA analysis is conducted for the mainshock-damaged buildings. The maximum interstory drift and residual drift IDA curves are developed and compared for both frames at different mainshock damage levels. The results are analyzed in terms of aftershock collapse capacity, collapse fragility, and collapse capacity at demolition. The effect of aftershock ground motion polarity on the performance of both frames is also explored. The study reveals that the SMRF has increased vulnerability to aftershocks when higher damages are induced during mainshock, while the aftershock collapse performance of the SVD frame is not affected from the intensity of mainshock event. It is also shown that the SVD frame significantly improves the aftershock capacity associated to a residual story drift that leads to major alignment or demolition.